Growth is Disappearing and May Not Recover in the Medium Run - Gligorov, Vladimir (World Bank, 2012)
Countries in Central, Eastern and South Eastern Europe have been hit hard by the global crisis. There is a need to rethink the growth model because a return to the status quo ante does not seem realistic.